2007
DOI: 10.1590/s0101-31222007000100001
|View full text |Cite
|
Sign up to set email alerts
|

Sementes esverdeadas em soja: testes alternativos para determinar a sua qualidade

Abstract: RESUMO -A comercialização antecipada de soja é uma realidade em Mato Grosso. Isso implica na necessidade de testes rápidos, confiáveis e que permitam minimizar riscos futuros, principalmente, quando existe um agente complicador a armazenabilidade, como é o caso de sementes com retenção de clorofila. Mudanças associadas à deterioração com conseqüente perda de vigor e viabilidade são observadas nesse tipo de semente, fazendo-se necessário o conhecimento da localização e abrangência dos pontos deteriorativos. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
1
4
0
4
Order By: Relevance
“…In their study, ZORATO et al, (2003) andARRUDA et al, (2016) reported similar results by the presence of the green seeds found in class 3 (average vigor), but especially in classes 4 and 5 (viability). The greenish seeds are reported to be responsible for inducing seed death in substantial amounts (DU 6-8) (Table 2).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…In their study, ZORATO et al, (2003) andARRUDA et al, (2016) reported similar results by the presence of the green seeds found in class 3 (average vigor), but especially in classes 4 and 5 (viability). The greenish seeds are reported to be responsible for inducing seed death in substantial amounts (DU 6-8) (Table 2).…”
Section: Resultssupporting
confidence: 54%
“…Earlier studies highlighted the fact that the green seeds present in the soybean seed lots have induced the decline in their physiological potential (ZORATO et al, 2007;CICERO et al, 2009;FRANÇA NETO et al, 2012;BROWN, 2017). Although, several studies revealed a negative correlation between the presence of green soybean seeds and seed quality, no clear evidence is available as yet on the influence exerted by the chlorophyll on seeds (TEIXEIRA et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Of note, isocitrate-lyase is considered a key enzyme in the regulation of the glyoxylate cycle, and it is also involved in the metabolism of stored lipids and the development of glyoxysomal activity. Insoluble lipids found in seeds are converted into soluble sugars (sucrose) via the glyoxylate cycle; then they are easily transferred to the roots and apical meristems (Zorato et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A isocitrato liase é uma enzima participante do ciclo do glioxilato, pertencente ao metabolismo de lipídios (Zorato et al 2007). Segundo Sant'anna (2005), sementes de abóbora possuem alto teor de lipídios (28,80 g%), sendo este a base do material de reserva para o processo germinativo.…”
Section: Figura 5 Primeira Contagem De Germinação (A) E Condutividadunclassified